The economic and social impacts of girls' primary education in developing countries - Floro, M.; Wolf, J. M. (Washington, D.C., Agency for International Development [USAID], Office of Education and Women in Development, 1990)
Policy in many countries of Africa, Asia, and Latin America has aimed to improve and extend public access to education. Countries have been moderately successful in achieving this goal. Over the period 1965-85, primary school enrollment in developing countries increased from 298 million to 482 million. School-age population, however, increased from 372 million to 527 million over the same period. 145 million school-age children did not have access to primary education in 1985. Accordingly, greater strides must be made in expanding access to education in developing countries. Female students are especially underrepresented in schools. This paper reviews evidence from countries throughout the world attesting to the positive economic and social impacts of girls' primary education in developing countries. Education has direct and indirect positive effects on the economic and social well-being of women, families, communities, and countries. Overall impact originates from the interplay of social and economic outcomes, with the latter conditioned by prevailing economic, social, and cultural environments. Education brings new skills and attitudes to women which lead to higher levels of female labor force participation, increased access to training and credit, and greater production of nonmarketed goods. Women develop greater decision making power, literacy and cognitive skills, higher potential to improve health care within the family, a desire for fewer children, and an interest in educating them. While much remains to be learned about the various effects of female education, studies do suggest that age, type of economic policy, resource distribution, gender discrimination, social and cultural norms, and socioeconomic background affect the manner and degree to which women use education-acquired skills.
USAID Contract No. DPE-5832-Z-00-9032-00.
Includes bibliographical references (p.79-105)
Keywords: Women -- Education -- Developing countries; Culture; Decision Making; Developing Countries; Economics; Educational Status; Employment; Family Characteristics; Health Resources; Health Services Needs and Demand; Public Policy; Research; Schools; Social Change; Socioeconomic Factors; Women; Women's Rights; Behavior; Demography; Education; Health Manpower; Organization and Administration; Population; Population Characteristics; Psychology; Social Behavior; Social Class; Technical Report